Ribosome pausing in amylase producing Bacillus subtilis during long fermentation - Yaozu Han; Biwen Wang; Alberto Agnolin; Gaurav Dugar; Frans van der Kloet; Christopher Sauer; Paul Igor Costea; Max Fabian Felle; Mathis Appelbaum; Leendert W. Hamoen (Microbial Cell Factories)
Abstract Background Ribosome pausing slows down translation and can affect protein synthesis. Improving translation efficiency can therefore be of commercial value. In this study, we investigated whether ribosome pausing occurs during production of the α-amylase AmyM by the industrial production organism Bacillus subtilis under repeated batch fermentation conditions. Results We began by assessing our ribosome profiling procedure using the antibiotic mupirocin that blocks translation at isoleucine codons. After achieving single codon resolution for ribosome pausing, we determined the genome wide ribosome pausing sites for B. subtilis at 16 h and 64 h growth under batch fermentation. For the highly expressed α-amylase gene amyM several strong ribosome pausing sites were detected, which remained during the long fermentation despite changes in nutrient availability. These pause sites were neither related to proline or rare codons, nor to secondary protein structures. When surveying the genome, an interesting finding was the presence of strong ribosome pausing sites in several toxins genes. These potential ribosome stall sites may prevent inadvertent activity in the cytosol by means of delayed translation. Conclusions Expression of the α-amylase gene amyM in B. subtilis is accompanied by several ribosome pausing events. Since these sites can neither be predicted based on codon specificity nor on secondary protein structures, we speculate that secondary mRNA structures are responsible for these translation pausing sites. The detailed information of ribosome pausing sites in amyM provide novel information that can be used in future codon optimization studies aimed at improving the production of this amylase by B. subtilis.